Data and Knowledge Modelling as the Methodological Foundation of the Digital Humanities - Gagarina, Dinara (Disegno. Journal of Design Culture, 2023)
Digital humanities is a multidisciplinary field that leverages digital technology and methodologies to explore and answer questions pertaining to the humanities. It is a dynamic intersection between the domains of computer science and the humanities, promoting innovation, collaboration, and research at the highest levels. However, as a relatively young field, the methodological foundations of the digital humanities are still being established. This paper seeks to explore the core methodologies that underpin digital humanities. The modelling of data, information, and knowledge can be considered one of the foundations of digital humanities. One of the arguments confirming this is that the development of digital humanities and the development of technologies in general are the development of ways to formalise and present data and knowledge. Science has come a long way from the modelling and computer representation of numbers to generating texts and art on the basis of prescribed inputs. With the advent of artificial intelligence, especially machine learning and deep learning techniques, the potential for more sophisticated and nuanced data modelling in the digital humanities has expanded significantly, linking computational capabilities with humanistic inquiries in unprecedented ways. The article considers the periodization, classification, and trends of approaches and methods for modelling data, information and knowledge in the humanities. The article provides an overview of existing examples and data models of different complexity from various humanities disciplines, including history, linguistics, literary criticism, and cultural studies.<br
Keywords: data modelling; knowledge representation; semantic networks; GPT; digital history

DEPUTIES WITH THE REPEATED PARLIAMENTARY STATUS IN LATE IMPERIAL RUSSIA: A CASE STUDY OF THE STATE DUMA OF THE 4TH CONVOCATION, 1912–1917 - Kiryanov, I. K.; Kornienko, S. I.; Gagarina, Dinara; Sotnik, A. V.; et al. (2017)

Digital Approaches for Studying Elected Representative Institutions in Late Imperial Russia - Ismakaeva, Iliana; Kornienko, Sergey; Gagarina, Dinara A; Senina, Anna (Science and Global Challenges of the 21st Century - Science and Technology. Perm Forum 2021. Lecture Notes in Networks and Systems, 2022)
Keywords: Digital history; History-oriented information systems; Digital humanities; Russian history; Representative institutions

Digital Humanities: an Educational Landscape - Gagarina, Dinara A; Kornienko, S. (ISTORIYA, 2020)
Keywords: Digital Humanities pedagogy; Digital humanities; Online course; Education; Teaching methods; Research infrastructures

DIGITAL OPTICS: MICRO AND MACRO IN HISTORICAL RESEARCH - Gagarina, Dinara A; Kornienko, Sergey Ivanovich (Perm University Herald. Series History, 2019)
The concept of “digital optics” is introduced in the article in relation to historical research. The content of the concept is revealed, and its characteristics are given. Digital optics is understood as a combination of approaches, methods, and tools based on digital technologies that allow researchers to “scale” the objects, events and periods under consideration, to study them in different time and spatial intervals, and to change these intervals within the same historical research. The article gives a general description of microhistory and macrohistory as methodological approaches and fields of historical research. This is done mainly based on historiographical works. The study drawsattention to the merits and limitations of the two approaches. The necessity of combining macro-and microhistorical approaches, methods and technologies in historical research, as well as the need for holistic knowledge and presenta-tion of history, are substantiated. This combination is considered both from the point of view of the possibility of reaching generalizations through microanalysis, and from the point of view of the possibility of understanding local events and objects through global optics. The foundations of digital optics and its methods are considered, and the examples of research and projects on different topics are given. The possibilities of digital optics and mathematical tools are revealed in micro-and macrohistorical studies, in overcoming their limitations, and in ensuring their unity. Digital optics methods are also analyzed from the perspective of the individual and the mass in history, in particular, through the processing of mass historical sources. The author also pay attention to the concept and methods of ana-lyzing big data in history.<br
Keywords: microhistory; digital history; macrohistory; digital optics; methodology of history; mathematical methods in history

Information Systems in the Digital Environment of Historical Studies - Gagarina, Dinara; Kornienko, Sergey; Povroznik, Nadezhda (Istoriâ., 2016)

Public History and the Digital Turn (The Russian Case) - Gagarina, Dinara; Imakaeva, Iliana (Public history weekly : blog journal for history and civics education, 2021)
Public and digital history in Russia is developing rather separately and in parallel to each other, these academic communities practically do not overlap. At the same time, a huge number of digital public history resources are being created. In the article, we consider some Russian features of public history in the context of digital turn, the actors of interaction between public and digital history, projects, as well as educational practices.<br
Keywords: Digital Change (Digitaler Wandel); Digital Humanities; Language: Russian; Russia (Russland)

Исторические информационные системы: теория и практика - Kornienko, Sergey Ivanovich; Gagarina, Dinara A; Povroznik, Nadezhda Georgievna (2021)
Historische oder historisch orientierte Informationssysteme sind ein wesentlicher Bestandteil der Informationsumgebung der Geisteswissenschaften. Seine Identifizierung ist mit der Entwicklung der historischen Informatik und eines historisch orientierten Ansatzes, der Bildung einer Informationsumgebung und der Praxis der Erstellung historischer Ressourcen verbunden. Das Buch enthält die Ergebnisse einer Untersuchung theoretischer und angewandter Probleme bei der Erstellung und Implementierung historisch orientierter Informationssysteme. Dies ist die erste umfassende Studie zu diesem Thema. Einige Probleme werden in dem Buch zum ersten Mal besprochen, während andere, obwohl sie zuvor in der Literatur berücksichtigt wurden, nicht speziell untersucht wurden. Die Veröffentlichung richtet sich an Historiker, Spezialisten auf dem Gebiet der digitalen Geschichte und der digitalen Geisteswissenschaften sowie an Entwickler digitaler Ressourcen, die historische Inhalte enthalten oder auf den Einsatz in der historischen Forschung und Bildung abziele